The Correction of Lysozyme in Mixed Saliva of Chronic Maxillary Sinusitis Patients with Oral Galvanosis - Tymofeiev, Олексій; Cherednichenko, А. М.; Tymofeiev, Олександр; Yaryfa, М. О. (Actual Dentistry, 2025)
Purpose: to determine the effectiveness of using a drug containing lysozyme hydrochloride to normalize the level of lysozyme enzyme in the mixed saliva of patients with chronic odontogenic maxillary sinusitis with oral galvanosis. Materials and Methods. 31 patients with chronic odontogenic maxillary sinusitis with galvanosis in the oral cavity were examined and underwent immunological and general clinical examination methods. Results. Based on the examination of patients with odontogenic maxillary sinusitis in the presence of galvanosis in the oral cavity, a temporary immunodeficiency was detected, which was eliminated by treatment with Lisobact®. In all operated patients in the early postoperative period, there was no such complication as the inflammatory infiltration of soft tissues in the postoperative wound area. Conclusions. The conducted examination gives us reason to recommend the drug “Lisobakt®” not only for normalizing the local nonspecific resistance of the body, but also allows you to eliminate the appearance of early inflammatory complications and reduce the development of late inflammatory complications (limited destructive osteomyelitis of the alveolar process of the upper jaw) by 2.5 times in the postoperative period of treatment of patients.